Oral manifestations and dental care management of a young patient with lymphangioma of the tongue: A case report - Chouchene, Farah (Clin Case Rep, 2021)
Children with lymphangioma of the tongue may require a close collaboration between physician and dentist to establish preventive, conservative approaches, and eradicate any sources of dental infections before undertaking immunosuppressive therapy.